Association Analysis of NALCN Polymorphisms rs1338041 and rs61973742 in a Chinese Population with Isolated Cervical Dystonia - Qingqing Zhou; Jing Yang; Bei Cao; Yongping Chen; Qianqian Wei; Ruwei Ou; Wei Song; Bi Zhao; Ying Wu; Huifang Shang (Parkinson's Disease)
Background. A genome-wide association study (GWAS) demonstrated a possible association between cervical dystonia (CD) and a sodium leak channel, nonselective (NALCN) gene. However, the association between NALCN and CD was largely unknown in Asian population. The present study was carried out to examine the associations between the two single nucleotide polymorphisms (SNPs) rs1338041 and rs61973742 in the NALCN gene and CD in a Chinese population. Methods. In a cohort of 201 patients with isolated CD, we genotyped the two SNPs rs1338041 and rs61973742 using polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP). We also included 289 unrelated, age- and sex-matched healthy controls (HCs) from the same region. Result. No significant differences were observed in either the genotype distributions or the minor allele frequencies (MAFs) of the two SNPs between the CD patients and the HCs. There were no significant differences between early-onset and late-onset CD patients, between patients with and without a positive family history of dystonia, or between patients with and without tremor or sensory tricks. Conclusion. Lack of association between the SNPs of NALCN and CD suggests that the SNPs of NALCN do not play a role in CD in a Chinese population.